Akad dalam Bentuk Transaksi Syariah - Nuha Nabila Aswari; Ahmad Rojalih Jawab (CV. Ulil Albab Corp, 2023)
As social creature, humans must understand the basic human need for social relations, namely the Tabbbaru Agreement, interacting and collaborating with other people in order to fulfill life’s needs. Several important points that can be dran from this are that human needs are diverse, including physical, emotional, social and psychological. Not all of these needs can be met indepently, and that drives humans to connect with other people. Then rights and obligations must also interact and relate to other people, there are rules that regulate rights and obligations, so these rules and can be fulfillerd inpendently, and that encourages humans to relate to other people. Rights and obligations in interacting and relating to other people, there are rules that regulate rights and obligations. These rules may vary according to the norms and values that apply in society, religion or applicable laws. Aggrements and contracts in transaction contracts to reach agreement in meeting mutual needs, people often carry out the process of entering into a contract carrying out the process of entering into a sharia transaction. A written agreement to have a mutually beneficial relationship. Furthermore, the nature and will of Allah SWT, this statement also implies the view that social relationships are part of human nature which has been destined by Allah SWT. In this context, fitrah refers to the basic nature of humans which directs them to interact in collaboration with fellow humans. This understanding reflects the imporentace of social relationships as part of humans nature which directs them to interact and collaborate with fellow humans. This understanding reflects the importance of social relations in human life and the need to have a legal and regulatory framework that regulates social interactions to maintain balance and justice in society. This also reflects the idea that humans are social intreactions to maintain balance and justiece in society. This also reflects the idea that humans are social creatures who naturally tend to interact wtith other people in order to fulfill their needs according to sharia.